Medical and Surgical Retina Recent Innovation, New Perspective, and Applications - Lo Giudice, Giuseppe (IntechOpen, 2023)
Knowledge of retinal diseases has radically changed over the past 10 years with the development of both new techniques and instrumentation, with improvements in surgical machines and diagnostic tools. This book reports the latest developments in retinal diseases, from pathogenesis to diagnosis, and both medical and surgical approaches in the management of retinal diseases. The core of the book focuses on developments and new perspectives in the treatment of some retinal diseases. It also discusses the pathophysiology and treatment of retinal diseases, taking biological disease markers into consideration. The indications for surgery have expanded dramatically and inoperable conditions have become amenable to surgical treatment. As such, the book also provides a comprehensive overview of the current state of the art in the surgical approach to many vitreoretinal diseases with the latest developments in surgery of the retina that enable improved surgical outcomes.